MANAJEMEN KEUANGAN DALAM MEMBANGUN KEMANDIRIAN PESANTREN DI PESANTREN DARUNNAJAH 2 CIPINING - Ricky Praditya Sukma Permana; Musthafa Musthafa; Nailil Muna Sholihah (CV. ALIM'SPUBLISHING, 2024)
Abstract. Educational institutions that are classified as having independence to a certain extent are Islamic boarding schools, both in terms of funding and in providing education. Not a few Islamic boarding schools have been able to properly implement the al-itimad principle a la alnafs, the al-najah principle, namely relying on oneself and optimizing one's potential as the basis for success, there are even some Islamic boarding schools that are able to empower the local economy. In this research, the researcher tries to take an approach that is closely related to what will be researched, where the approach is used as a reference in the research process. The method in this research is that the researcher uses qualitative data collection techniques with descriptive methods to provide a systematic description of the situation, facts and phenomena found in the location to be studied. The research results show that in its efforts to build the independence of Islamic boarding schools. To build the independence of Islamic boarding schools, not only with a vision and mission, it is necessary to have funds to support the Islamic boarding school. keywords: Management, financing and independence